The Effects of Reduced Graphene Oxide Flakes in the Dielectric on Electrical Discharge Machining - Świercz, Rafał (Nanomaterials (Basel), 2019)
Electrical discharge machining (EDM) is a nonconventional technology that is frequently used in manufacturing for difficult-to-cut conductive materials. Drawbacks to using EDM include the resulting surface roughness and integrity. One of the recent innovations for improving surface integrity with EDM is the use of a powder mixed dielectric. The aim of this study is to analyze the influence of having reduced graphene oxide (RGO) in the dielectric on the ionization of the plasma channel and the dispersion of electrical discharges. The main goal is to improve the surface integrity of the tool steel 55NiCrMoV7 during finishing machining. To achieve this goal, an experimental investigation was carried out to establish the smallest possible values of discharge current and pulse time at which it is possible to initiate an electric discharge, which causes material removal. Next, the effect of the direction of the electric discharges (electrode polarity) and the concentration (percentage) of RGO in the dielectric on surface integrity was investigated. The results of this experiment indicate that during EDM with RGO, the discharges are dispersed on the RGO flakes. This leads to a multiplication of the discharges during a single pulse, and this strongly affects the surface integrity. The obtained results indicate that it is possible to reduce surface roughness and thickness of the recast layer by approximately 2.5 times compared with conventional EDM.